READY TO CONQUER THE WORLD OF WORK: THE ROLES OF SELF-EFFICACY AND SOCIAL SUPPORT - Alya Ayu Purnama; Nur Ainy Sadijah; Regi Ramadan (CV. TOTUS TUUS, 2026)
Work readiness is essential for high school students who may enter employment immediately after graduation, particularly in industrial regions where youth unemployment remains high. This study examined whether self-efficacy and perceived social support predict work readiness among students at a public high school in Karawang, Indonesia. A quantitative correlational design was employed with a population of 1,284 students. Using stratified random sampling and the Krejcie-Morgan sample-size table, 296 students were selected. Data were collected using the Work Readiness Scale, the 12-item General Self-Efficacy Scale, and the Multidimensional Scale of Perceived Social Support. The instruments were reviewed through a tryout involving 31 respondents before the main data collection. Multiple linear regression was conducted with JASP. Self-efficacy significantly and positively predicted work readiness (t = 5.079, p < .001), and perceived social support was also a significant positive predictor (t = 2.963, p = .003). Jointly, both variables significantly predicted work readiness, F(2, 293) = 28.78, p < .001. The model explained 16.4% of the variance in work readiness (R² = .164), indicating that personal confidence and supportive relationships contribute to students' preparation for employment, although other career-related factors remain influential. Schools and families should therefore strengthen sustained career guidance, confidence-building activities, and supportive communication to improve students' transition into work.